Change ofÂ soil quality based onÂ humic acid withÂ date palm compost incorporation - Hadda Ben Mbarek; Imen Ben Mahmoud; Rayda Chaker; Hafedh Rigane; Sameh Maktouf; Aissa Arous; Nabil Soua; Mouna Khlifi; Kamel Gargouri (International Journal of Recycling of Organic Waste in Agriculture)
Purpose The most important factor affecting soil quality is soil humic fraction. Effects of adding carbon in soil humic compounds in arid environments have only been slightly investigated. The change in soil humic acidsâ structures in relation with manure and palm compost application and the evolution of humic acidsâ structures during palm composting have not been sufficiently investigated. The purpose of this study is to evaluate if date palm compost is suitable for the sustainable increase of soil carbon content with increasing soil humic compounds. Methods Soil was amended with date palm compost and sheep manure, which represented two treatments, in addition to a control represented by unamended soil. Soil samples were taken from depth layers of 0â20 cm and 20â40 cm. Physicochemical and spectroscopic analyses were used to study humic acids extracted from organic amendment and soil. Results The neutral pH and the C/N ratio of 11.9 revealed that the palm/manure compost was mature. Date palm compost application on soil showed its effectiveness in improving soil quality. Spectroscopic studies of humic compounds extracted from date palm compost and manure, showed the abundance of aromatic structures, confirmed by the low E4/E6 ratio associated with an increase in polycondensation and polymerization. Infrared spectroscopy of humic acids extracted from amended soil revealed its enrichment with aromatic structures. Conclusions Using date palm compost for a short term suggests that this compost may be useful as an alternative to increase the soil fertility by increasing the humic acids quantity with enhancing aromaticity degree and functional groups.